Cauda equina enhancing lesion in a HIV-positive patient. Case report and literature revision. - Pasquale De Bonis; Antonella Cingolani; Angelo Pompucci; Tommaso Tartaglione; Luigi Maria Larocca; Luciana Teofili (Mediterranean Journal of Hematology and Infectious Diseases)
We describe the case a spinal cord localization of neurological toxoplasmosis in a HIV-positive patient with Burkitt lymphoma, previously treated with chemotherapy and immunotherapy. This complication occurred while patient was in complete remission of lymphoma, with CD4+ T cell count of 270 /ml, undetectable HIV viremia, and despite the trimethoprim/ sulfamethoxazole prophylaxis. Indeed, we hypothesize that in our patient neurologic toxoplasmosis has been fostered more by previous immuno-chemotherapy than by HIV- related immunodeficiency. On the whole, this case suggests that parameters usually employed to predict the risk for opportunistic infections in HIV-positive people might not apply to patients with HIV-related lymphomas.